Entwicklungstendenzen der innerstädtischen Zentralität: Das Beispiel Bonn - Waldhausen-Apfelbaum, Jeanette; Grotz, Reinhold (ERDKUNDE, 1996)
Although CHRISTALLER developed his model of central places for entire cities and their rural environs, in Germany it is also used for inner-city hierarchies, and serves as a basis for city planning. This paper deals with the hierarchy of centers within the city of Bonn, and it also includes the results of studies from other cities. Retail and service supplies are compared on different levels as well as an examination of the shopping orientation of customers. Results show that distinctions within the hierarchy are blurred. It is becoming increasingly difficult to find a clear relation between areas to be serviced and their centers on different levels. New locations and new forms of supply behaviour are responsible for this. Customers are shopping specifically, according to commodities which is enabled by a higher capability and willingness for mobility. The CBD suffers from congestion, noise pollution, and confusion. Therefore, some groups of customers reduce their frequency of visits. Finally, an outline of the spatial and functional patterns of locations is offered, which includes new service centers at the outskirts of cities. It stresses the need for the inclusion of new, large-scale shops in a farsighted and comprehensive planning system instead of prohibiting such new shops as was done in the past.